The Relationship of Self-care and Health Literacy with Mental Health among Citizens of Tabriz City - Mohammad Bagher Alizadeh Aghdam; Kamal Koohi; Mohammad Gholizadeh (Kerman University of Medical Sciences, 2017)
Background & Objectives: The importance of mental health in personal and social life of people as well as the high cost of health services in today's world necessitates people to attempt for acquiring personal skills for maintaining and improving their health. In this regard, self-care and health literacy, as dynamic and available tools for individuals, can play a decisive role in promoting equity in mental health. Methods: This study was a descriptive-analytic study performed on 414 citizens over 15 years of age in Tabriz, Iran who were selected through multi-stage cluster sampling. Data gathering was done using general health questionnaire with three dimensions, literacy questionnaire consisted of five dimensions of reading comprehension, access, understanding, evaluation and decision making and a researcher-made questionnaire about self-care. Data analysis was performed using t-test, Fisher test, Pearson correlation coefficient and multivariate linear regression and through SPSS22 software. Results: Mean score of mental health was 58.38, mean score of self-care was 54.46 and mean score of health literacy was 77.20. There was a significant and direct relationship between mental health and variables of age, marital status, education level, and self-care. Conclusion: The present study emphasizes on the importance of training on and accepting responsibility for mental health. People can maintain and improve their health and accept responsibility in this regard through acquiring sufficient knowledge on health aspects. Keywords: Health literacy, Self-care, Mental health, Citizens Citation: Alizadeh Aghdam MB, Koohi K, Gholizadeh M. The relationship of Self-care and Health Literacy with Mental Health among Citizens of Tabriz City. Journal of Health Based Research 2017; 2(4): 381-394.